ABSORPTION CO2 GAS USING MONOETHANOLAMINE - Ricky Priambodo2), Sylvia Purnomo3), Hermawan Sutanto4), Wentalia Widjajanti5), Endang Srihari 1) , (Jurnal Teknik Kimia, 2011)
The air on an area of solid industry, having a level pollution that high . it is muchcaused the process of combustion done by most of the industry , whereby on the process ofcombustion will be produced a gas of dioxide carbon ( CO2 ) that edangers . Hence , requireda method to depress figures pollution resulting from the womb overgrowth CO2 in the air the ,one of them is with the process of absorption .CO2 absorption process usingmonoethanolamine (MEA) performed in a packed column absorber aims to determine the priceof overall volumetric mass transfer coefficient of the gas phase to the variable operation andknow the value of the interfacial area per unit volume packing (a) of the price of the coefficientvolumetric mass transfer. CO2 gas flowing to the packed column using MEA as a solvent. Theresults are overall volumetric mass transfer coefficient of the gas phase, KGa the greater therate of CO2 gas at a constant flow rate of MEA and its getting bigger. Likewise, under the sameconditions, the price of interfacial area per unit volume will increase packing. But at aconstant rate of MEA with greater gas flow rate of CO2 will cause the overall mass transfercoefficient of the gas phase, KGa decreases. While at the greater concentration of MEAsolution will cause the KGa is increasing. The interfacial area per unit volume packing is notaffected by changes in gas flow rate and concentration of MEA.Key words: Absorption of CO2,, Monoethanolamine, overall volumetric mass transfercoefficient of gas phase, interfacial area per unit volume packing